Supervision of Structured Waste Management System Based on Separate Collection Scheme as Strategy for Economic Empowerment of The Community of Melong Village, Cimahi City - Dzaky CP, Vicky; Hartikayanti, Heni Nurani; Maryani, Neni; Rahmah, Nunung Aini; Sastradipraja, Usman; Larasati, Anissa Yuniar; Purwanto; Binekas, Bani; Hartika, Wiwi (International Journal of Research in Community Services, 2025)
The increasing volume of waste in Cimahi City has become an environmental and socio-economic challenge that demands sustainable and community-based management. This community service project aims to strengthen environmental awareness and economic empowerment through the implementation of a Structured Waste Management Monitoring System based on the Separate Collection Scheme (SKP) and the 4R principles (Replace, Reduce, Reuse, Recycle) in RW 07, Melong Village. The program uses a participatory approach that combines field surveys, workshops, and mentoring involving local residents, academics, and government representatives. Activities began with a situation analysis and coordination with the Melong Village Government, followed by educational sessions and practical demonstrations on waste sorting, recycling, and monitoring practices. Pre-test and post-test assessments showed a significant increase in residents' understanding of waste classification, monitoring mechanisms, and sustainable waste management practices. The implementation of the SKP model successfully drove behavioral change, fostered collective responsibility, and reduced dependence on municipal waste services. Furthermore, this initiative generated socio-economic benefits by motivating residents to develop recycling-based entrepreneurship such as waste banks, composting, and creative recycled products. The research findings demonstrate that integrated environmental education and participatory monitoring can effectively drive community transformation toward sustainability. Collaboration between academics, local government, and the community has resulted in a replicable model for structured, community-based waste management that contributes to environmental protection and economic resilience. In conclusion, this program not only addresses the local waste crisis but also lays the foundation for a circular economy framework at the village level, supporting Cimahi City's vision for a clean, resilient, and sustainable urban ecosystem. Keywords: Community empowerment, separate collection scheme, waste management, circular economy, Cimahi City